Hyaluronic acid-based nanofibers: Electrospun synthesis and their medical applications; recent developments and future perspective - Humaira,; Raza Bukhari, Sayyad Ali; Shakir, Hafiz Abdullah; Khan, Muhammad; Saeed, Shagufta; Ahmad, Irfan; Muzammil, Khursheed; Franco, Marcelo; Irfan, Muhammad; Li, Kun (Frontiers in Chemistry, 2022)
Hyaluronan is a biodegradable, biopolymer that represents a major part of the extracellular matrix and has the potential to be fabricated in a fibrous form conjugated with other polymers via electrospinning. Unique physicochemical features such as viscoelasticity, conductivity, and biological activity mainly affected by molecular weight attracted the attention of biomedical researchers to utilize hyaluronan for designing novel HA-based nano-devices. Particularly HA-based nanofibers get focused on a diverse range of applications in medical like tissue implants for regeneration of damaged tissue or organ repair, wound dressings, and drug delivery carriers to treat various disorders. Currently, electrospinning represents an effective available method for designing highly porous, 3D, HA-based nanofibers with features similar to that of the extra-cellular matrix making them a promising candidate for designing advanced regenerative medicines. This review highlights the structural and physicochemical features of HA, recently cited protocols in literature for HA production via microbial fermentation with particular focus on electrospun fabrication of HA-based nanofibers and parameters affecting its synthesis, current progress in medical applications of these electrospun HA-based nanofibers, their limitations and future perspective about the potential of these HA-based nanofibers in medical field.